2011
DOI: 10.1002/jsfa.4248
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic and conventional growth systems on the content of carotenoids in carrot roots, and on intake and plasma status of carotenoids in humans

Abstract: The expected higher content of presumed health-promoting carotenoids in organic food products was not documented in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 47 publications
5
49
1
1
Order By: Relevance
“…The daily intake of nutrients can be calculated taking into account daily intakes of carrots, which has been estimated at 173 g (Soltoft et al, 2010). The RDI for potassium is 200 mg day À1 (Czech Republic, 2008).…”
Section: The Carrot Contribution To the Rdismentioning
confidence: 99%
See 2 more Smart Citations
“…The daily intake of nutrients can be calculated taking into account daily intakes of carrots, which has been estimated at 173 g (Soltoft et al, 2010). The RDI for potassium is 200 mg day À1 (Czech Republic, 2008).…”
Section: The Carrot Contribution To the Rdismentioning
confidence: 99%
“…Generally, organic foods are perceived as healthier and safer than conventional foods. Moreover, organic production is believed to provide agronomic and environmental benefits, such as the preservation of natural resources and reduction in air, water, soil and food pollution (Domagała-Ś wią tkiewic z & Herencia, Garcia-Galavis, Dorado, & Maqueda, 2011;Soltoft et al, 2010). Similarly, organic foods may have other advantages, such as the ingestion of more phenolic compounds and vitamins, and less nitrates and pesticides (Lima & Vianello, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the impact of organic and conventional agricultural systems on the carotenoid content in carrots and human diets found that the plasma status of carotenoids in humans increased significantly after the consumption of both organic and conventional crops, observing no systematic differences between the agricultural production systems [37]. However, more studies are required to study carotenoids from a standpoint of bioavailability and bioaccessibility.…”
Section: Quantitation Of Individual Polyphenols In Conventional and Omentioning
confidence: 99%
“…Studies comparing chemical composition of conventionally and organically grown vegetables have mainly focused on nutrients, 8,9,13 and selected secondary metabolites such as carotenoids, polyacetylenes, and phenolic acids. 6,14,15 However, studies are lacking which compare the eating quality of conventionally and organically grown vegetables under comparable field conditions. 11 In organic vegetable production, synthetic pesticides are banned and the type and intensity of fertilization is restricted with the aim of making less impact on the environment.…”
mentioning
confidence: 99%